AGENSI PEREMPUAN DALAM POLEMIK PRAKTIK PEMOTONGAN DAN PERLUKAAN PADA GENITAL PEREMPUAN (P2GP) - Hikmalisa (Jurnal Sosiologi Agama, 2022)
Female genital mutilation (FGM), widely criticized from various circles such as WHO and UN, remains prevalent until today. A village in Kampar regency, an area with a Muslim Majority, is one of the largest areas that implements circumcision in the provence of Riau. Women are conventionally seen as passive and uncritical actors in the perpetuation of this practice. This research attempts to reveal women’s agency in the practice of FGM. Based on more than a month of field research in the village in Kampar regency, this paper employs a descriptive-qualitative approach. Data were obtained using involved observations, interviews, and a review of local histories and customary law. Using Bourdieu’s structural genetic theory, this paper explains the ways in which different socially-located women use their agency to critically ingage with FGM practices within their specific arena. I argue that women—women as mothers, women as children, and women as medical personnel—are active and critical agents vis-a-vis FGM practices. Using the capital they have within the arena in which they live, women exercise their agencies in the different ways to achieve certain goals. Women with high capital in certain arenas, especially in the family, will have more ability to resist FGM. On the other hand, women with low capital can also negotiate to perform symbolic circumcision, even if the habitus associated with circumcision does not change. As medical professionals, midwives also exercise agency by refusing to perform FGM on girls, but if forced to do so , they will usually perform minor circumcisions to fulfill the habitus of the practice in a symbolic way.